The Filling Discs Dealing with Multiple Values of an Algebroid Function in the Unit Disc - Zu-Xing Xuan; Nan Wu (Abstract and Applied Analysis)
In this paper, by using the potential theory we prove the existence of filling discs dealing with multiple values of an algebroid function of finite order defined in the unit disc.